Investigation on the formation of herringbone structure in type II solar radio bursts - Abidin, Zamri Zainal (Natl Astronomical Observatories, Chin Acad Sciences, 2023)
We report detailed observation of the ``herringbone'' of a Type II solar radio burst that occurred on 2010 November 3rd. Data from the Space Weather Prediction Center, National Oceanic and Atmospheric Administration, e-CALLISTO, and Nancay RadioHeliograph are analyzed. We determine the brightness temperature and degree of circular polarization of the ``herringbone'' burst. Correlations between the physical parameters and the ``herringbone'' are examined. Based on the relationship, this is the first study that suggested this ``herringbone'' was generated through fundamental plasma.